Elvis' Gospel Music: Between the Secular and the Spiritual? - Duffett, Mark (Religions, 2015)
Do fans sanctify their heroes? In the past, I have argued that Elvis fandom is not a neo-religious practice but that attention to a modified version of Durkheim's theory of religion can, nevertheless, help to explain it as a form of social interaction. I take that argument further here, first by revealing the ethical and analytical advantages of neo-Durkheimian theory, then by pitting this theory against three aspects of Elvis' sincere engagement with gospel music. Elvis Presley won three Grammy awards for his gospel albums and was the musician who did most to bring the gospel quartet tradition to the mainstream. His eclectic personal ties to spirituality and religion have become a focus of debate within his fan culture. They offer a set of discursive resources through which to explain the emotional impact and social influence of his music. If star musicians are positioned as centres of attention, what happens when they use their privileged position in the spotlight to offer a spiritual message?